SPIRITUALITAS KRISTEN DI ERA POSTMODERN - Harefa, Febriaman Lalaziduhu (Manna Rafflesia)
As the times progress from modern to post-modern, the principle of life also begins to change in accordance with the times, so does human spirituality, how do Christian attitudes judge the age and face this age? What kind of spirituality should be applied by believers? Considering the knowledge of Christian Spirituality in the Postmodern Era is very important, it is therefore necessary to provide an understanding of the insights of Christian spirituality, so that believers can wisely support this age.